2009
DOI: 10.1148/radiol.2503080995
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma: Dynamic Contrast-enhanced MR Imaging for Differentiation of Tumor Subtypes—Correlation with Pathologic Findings

Abstract: Clear cell, papillary, and chromophobe RCCs demonstrate different patterns of enhancement on two-time point clinical dynamic contrast-enhanced MR images, allowing their differentiation with high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(195 citation statements)
references
References 51 publications
9
181
1
4
Order By: Relevance
“…A potential alternative to increased use of biopsy might lie in the use of diagnostic imaging to characterize renal cortical tumors on the basis of their tissue composition, morphologic features, and/or contrast enhancement patterns (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Doppler ultrasonography, contrast material-enhanced computed tomography, and magnetic resonance (MR) imaging have shown potential for enabling differentiation of clear cell renal carcinomas (which show increased vascular flow and enhance avidly) from papillary and chromophobe carcinomas (which show reduced vascular flow and less enhancement) (21)(22)(23)(24)(26)(27)(28)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential alternative to increased use of biopsy might lie in the use of diagnostic imaging to characterize renal cortical tumors on the basis of their tissue composition, morphologic features, and/or contrast enhancement patterns (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Doppler ultrasonography, contrast material-enhanced computed tomography, and magnetic resonance (MR) imaging have shown potential for enabling differentiation of clear cell renal carcinomas (which show increased vascular flow and enhance avidly) from papillary and chromophobe carcinomas (which show reduced vascular flow and less enhancement) (21)(22)(23)(24)(26)(27)(28)).…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasonography, contrast material-enhanced computed tomography, and magnetic resonance (MR) imaging have shown potential for enabling differentiation of clear cell renal carcinomas (which show increased vascular flow and enhance avidly) from papillary and chromophobe carcinomas (which show reduced vascular flow and less enhancement) (21)(22)(23)(24)(26)(27)(28)). Yet despite the encouraging early results, imaging diagnosis and particularly differentiation of benign and malignant histologic subtypes of renal cortical tumors remains problematic, and further studies with multiple independent readers are needed to assess the diagnostic performance of imaging in this clinical context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[94] In addition, clear cell RCC has a strong association with necrosis and retroperitoneal collateral circulation that is best seen on MRI [95]. On the other hand, papillary RCCs show homogeneous low-level enhancement on both CT and MRI [94,96]. This will be discussed in detail for each type of imaging modality.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…MR study of enhancement patterns of the clear cell, papillary, and chromophobe forms of renal cell carcinoma has been performed, showing some distinctive enhancement patterns for each of the three subtypes, however, no comparison was made to oncocytoma, the benign tumor that is of critical consideration in this differential diagnosis. [94] Studies also have shown that papillary RCCs are hypointense on T2-weighted imaging, likely due to old blood products, whereas clear cell RCCs tend to be T2 iso-to hyperintense. Though enhancing renal masses are reliably detected on MRI, renal cell tumor subtyping has not been as extensively investigated in a manner similar to that of CT.…”
Section: Magnetic Resonance Imaging and Differentiation Of Renal Massesmentioning
confidence: 99%